Implication of Macroeconomic Fundamentals on the Twin-Evil of Macroeconomic Phenomena: “With the Focus on Nigeria” - Topbie, Joseph Akeerebari; Anyamaobi, Godgift Nwankwo; Lasisi, Olapade Kehinde (International Journal of Humanity and Social Sciences, 2024)
Purpose of the Study: This study was designed to analyze the implication of Macroeconomic fundamentals on twin-evil of Macroeconomic phenomena: “with the focus on Nigeria.’’ Methodology: The study Utilized annual time-series data on exogenous variables (Government Deficit Spending, GDS; Official exchange rate, OEXCHR; Monetary policy rate, MPR) to capture Macroeconomic fundamentals. While, Unemployment rate, UNEMPLR; Inflation rate, INFLR and Consumer price index, CPI were used as a summation of Macroeconomic phenomena to capture Misery index. The data on variables used in the study were sourced from Nigerian federal ministry of finance; Central Bank of Nigeria; and World Bank data bank between 1991and 2022 respectively. The study employed econometric techniques of ordinary least square and Two-stage least to analyze its data. Findings: The study of Ordinary Least Square revealed that Government deficit spending and official exchange rate significantly eradicate misery index in a positive manner. Meanwhile, monetary policy rate insignificantly eradicate misery index in a negative manner. There was also a further revelation from the findings of two-stage least square that government deficit spending and official exchange rate exert concerted significant strength to eradicate misery from every citizen of Nigeria within the periods under study.. Meanwhile, the result found that it was insignificantly weak for monetary policy rate (MPR) to minimize misery index from every Nigerian citizen within the periods under study. Unique Contribution to Theory, Practice and Policy: The study concluded that the authority should maintain a sound policy that will oversee money borrowed for critical projects and use it to create employment opportunity for Nigerian citizenry, ensure exchange rate is kept within a certain band that will reduce high cost of goods and services in the economy that we are currently facing and jettison the idea of increasing monetary policy rate, since this displayed a negative sign to help reducing misery index of the Nigerian populace during the periods of study.